Ethnoveterinary plant preparations as livestock dewormers: Practices, popular beliefs, pitfalls and prospects for the future - Githiori, J.B.; Höglund, J.; Waller, P.J. (Cambridge University Press, 2005)
Ethnomedicine is an integral part of traditional medical practices in many countries of the developing world. A large proportion of the population uses this form of treatment for primary health care and for the treatment of ailments in their livestock. Livestock is a major asset for resource-poor smallholder farmers and pastoralists throughout the world and internal parasites are recognized by these communities as having an impact on livestock health. Parasitic infections are among those infections that traditional healers confidently treat and against which an enormous variety of remedies exist. Many of these are based on the use of plant preparations. Although various methods have been used for the validation of traditional phytomedical preparations, there is a lack of standardization of these procedures. The present study is aimed at providing an overview of ethnoveterinary deworming preparations, the various methods that have been used in their validation and the future prospects for their use against helminth parasites of ruminant livestock in developing countries, with an emphasis on nematode parasites. Recommendations are made on the procedures that should be followed to conduct in vivo and in vitro assays. Fostering better interaction between traditional healers and scientists is advocated to prevent harmful overexploitation, both of local knowledge and of plant species that may have effects against nematode parasites.